Population Pharmacokinetics of Caspofungin and Dosing Optimization in Children With Allogeneic Hematopoietic Stem Cell Transplantation - Niu, Chang-He; Xu, Hua; Gao, Liu-Liu; Nie, Ying-Ming; Xing, Li-Peng; Yu, Li-Peng; Wu, San-Lan; Wang, Yang (Frontiers in Pharmacology, 2020)
Caspofungin is the first echinocandin antifungal agent that licented for paediatric use in invasive candidiasis and aspergillosis. In this study, we evaluated the population pharmacokinetics of caspofungin and investigate approprite dosing optimization against Candida spp. in children with allogeneic hematopoietic stem cell transplantation (allo-HSCT) in order to improve therapeutic efficacy. All participants received a recommended caspofungin 70 mg/m2 loading dose followed by 50 mg/m2 maintenance dose. A one-compartment model with first-order elimination was best fitted the data from 48 pediatric patients. Body surface area and aspartate aminotransferase had significant influence on caspofungin clearance from covariate analysis. Our results reviewed that dose adjustment is not nescessary in patients with mild liver dysfunction. Monte Carlo simulations were performed using pharmacokinetic data from our study to evaluate the probability of target attainment (PTA) of caspofungin regimen in terms of AUC24/MIC targets against Candida spp. The results of simulations predicted that a caspofungin 70 mg/m2 at first dose, 50 mg/m2 of daily dose may have a high probability of successful outcome against C.albicans and C.glabrata whilst 60 mg/m2 maintenance dose was required for fungistatic target against C.parapsilosis but may be not sufficient to achieve optimal fungicidal activity. Caspofungin standard regimen had high probability of successful outcome against C.albicans (MIC≤0.25 mg/L) and C.glabrata (MIC≤0.5 mg/L) but insufficient for C.parapsilosis with MIC≤0.25 mg/L. That may provide an evidence based support to caspofungin individualized administration and decrease the risk of therapeutic failure in allo-HSCT pediatric patients.